ADP Plays a Key Role in Thrombogenesis in Rats - Maffrand, J P; Bernat, A; Delebassée, D; Defreyn, G; Cazenave, J P; Gordon, J L (Thrombosis and Haemostasis, 1988)
The relative importance of ADP, arachidonic acid metabolites and serotonin as thrombogenic factors was evaluated in rats by comparing, after oral administration, the effects of two inhibitors of ADP-induced platelet aggregation (ticlopidine and PCR 4099), three cyclo-oxygenase inhibitors (aspirin, triflusal and indobufen) and a selective serotonin 5HT2 receptor antagonist (ketanserin) on platelet aggregation, in four platelet-dependent thrombosis models and on bleeding time. Platelet aggregation induced by ADP and collagen was completely inhibited by ticlopidine and PCR 4099 whereas only the collagen aggregation was reduced by the cyclo-oxygenase inhibitors. Ketanserin or a depletion of platelet serotonin by reserpine did not affect platelet aggregation. Ticlopidine and PCR 4099 greatly prolonged rat tail transection bleeding time. This is probably related to their known ability to inhibit ADP-mediated platelet aggregation. In contrast, the cyclooxygenase inhibitors did not affect bleeding time at all. Reserpine and ketanserin prolonged bleeding time by interfering with the action of serotonin on the vascular wall. Ticlopidine and PCR4099 were very potent antithrombotics in all the models. Aspirin, only at a high dose, inhibited poorly thrombus formation on a silk thread in an arterio-venous shunt, suggesting that the inhibition of cyclo-oxygenase was not responsible. Triflusal was inactive in all models while indobufen slightly reduced thrombus formation in the silk thread and metallic coil models. Ketanserin and reserpine reduced thrombus only in the metallic coil model. Thrombus formation was greatly reduced in fawn-hooded rats, which lack ADP in their platelet dense granules because of a genetic storage pool deficiency. Taken together, the results obtained with the drugs and with the fawn-hooded rats support the concept that ADP plays a key role in thrombogenesis in rats.
Keywords: Fawn-hooded rat; Platelet aggregation; Thrombosis; Ticlopidine; PCR 4099; Aspirin; Triflusal; Indobufen; Ketanserin